Cholesterol and HIF-1α: Dangerous Liaisons in Atherosclerosis - Thomas, Charles; Leleu, Damien; Masson, David (Frontiers in Immunology, 2022)
HIF-1α exerts both detrimental and beneficial actions in atherosclerosis. While there is evidence that HIF-1α could be pro-atherogenic within the atheromatous plaque, experimental models of atherosclerosis suggest a more complex role that depends on the cell type expressing HIF-1α. In atheroma plaques, HIF-1α is stabilized by local hypoxic conditions and by the lipid microenvironment. Macrophage exposure to oxidized LDLs (oxLDLs) or to necrotic plaque debris enriched with oxysterols induces HIF-1α -dependent pathways. Moreover, HIF-1α is involved in many oxLDL-induced effects in macrophages including inflammatory response, angiogenesis and metabolic reprogramming. OxLDLs activate toll-like receptor signaling pathways to promote HIF-1α stabilization. OxLDLs and oxysterols also induce NADPH oxidases and reactive oxygen species production, which subsequently leads to HIF-1α stabilization. Finally, recent investigations revealed that the activation of liver X receptor, an oxysterol nuclear receptor, results in an increase in HIF-1α transcriptional activity. Reciprocally, HIF-1α signaling promotes triglycerides and cholesterol accumulation in macrophages. Hypoxia and HIF-1α increase the uptake of oxLDLs, promote cholesterol and triglyceride synthesis and decrease cholesterol efflux. In conclusion, the impact of HIF-1α on cholesterol homeostasis within macrophages and the feedback activation of the inflammatory response by oxysterols via HIF-1α could play a deleterious role in atherosclerosis. In this context, studies aimed at understanding the specific mechanisms leading to HIF-1α activation within the plaque represents a promising field for research investigations and a path toward development of novel therapies.